Correlation between Hox code and vertebral morphology in archosaurs - Böhmer, Christine (Proc Biol Sci, 2015)
The relationship between developmental genes and phenotypic variation is of central interest in evolutionary biology. An excellent example is the role of Hox genes in the anteroposterior regionalization of the vertebral column in vertebrates. Archosaurs (crocodiles, dinosaurs including birds) are highly variable both in vertebral morphology and number. Nevertheless, functionally equivalent Hox genes are active in the axial skeleton during embryonic development, indicating that the morphological variation across taxa is likely owing to modifications in the pattern of Hox gene expression. By using geometric morphometrics, we demonstrate a correlation between vertebral Hox code and quantifiable vertebral morphology in modern archosaurs, in which the boundaries between morphological subgroups of vertebrae can be linked to anterior Hox gene expression boundaries. Our findings reveal homologous units of cervical vertebrae in modern archosaurs, each with their specific Hox gene pattern, enabling us to trace these homologies in the extinct sauropodomorph dinosaurs, a group with highly variable vertebral counts. Based on the quantifiable vertebral morphology, this allows us to infer the underlying genetic mechanisms in vertebral evolution in fossils, which represents not only an important case study, but will lead to a better understanding of the origin of morphological disparity in recent archosaur vertebral columns.